Anthony Ashley Cooper Shaftesbury: Philosophy - Grzeliński, Adam; Płoski, Jakub (Folia Philosophica, 2024)
The Polish translation titled Philosophy is part of the philosophical notebooks of Anthony Ashley Cooper, the Third Earl of Shaftesbury (1671–1713). Alongside other passages that explore nature, goodness, and beauty, it summarizes the reflections developed during Shaftesbury’s time in the Netherlands. His opposition to religious fanaticism, emphasis on interpersonal bonds, and engagement with social and political issues position him as a thinker associated with Enlightenment thought. However, this article argues that the author of Characteristics of Men, Manners, Opinions, Times was more closely aligned with ancient philosophical ideals. For Shaftesbury, philosophy was not primarily a theoretical inquiry into nature or human beings; rather, he regarded it as a practical guide to life – one that shapes fundamental human choices and cultivates a sound understanding of values.